The last kingdom. Season one [videorecording (DVD)] - Murphy, Nick; Byrne, Anthony, 1975-; Dreymon, Alexander; Hart, Ian, 1964-; Dawson, David, 1982-; Cornwell, Bernard (Universal Pictures Home Entertainment, 2017)
The people of the small village of Wessex stand up and fight against the Viking invasion that threatens the entire land.